(untitled) (CIPEEX, 2025)
Spirituality, understood as an existential dimension, constitutes an essential element of human experience, as it is linked to the search for meaning, purpose, and transcendence. This dimension holds significant relevance by fostering the integration of mind, body, and emotions, providing inner balance and resilience in the face of everyday challenges. In this context, the present text emerged from an academic seminar developed within the discipline Citizenship, Ethics, and Spirituality, in the Business Administration program, whose central purpose was to reflect on spirituality as an experience capable of bringing human beings closer to transcendence and the construction of life’s meaning. The proposal sought to understand how different religious traditions influence personal formation, social coexistence, and ethical practice in multiple scenarios. The main objective was to analyze how spiritual principles can contribute to the promotion of values such as empathy, solidarity, and social responsibility, both at the individual and collective levels. The methodological approach involved a literature review, guided readings of doctrinal texts, classroom discussions, and comparative analyses of religious practices, prioritizing the identification of universal values and the consideration of the specificities of each tradition. The results showed that, although distinct in doctrine and practice, the religions studied share common foundations such as love for one’s neighbor, charity, the importance of faith, and the pursuit of personal improvement, aspects that prove indispensable for building fairer and more collaborative human relationships. Among the main challenges, the need to reconcile diverse perspectives without disregarding the uniqueness of each belief stood out, requiring a critical stance and openness to dialogue. It is concluded that spirituality, when lived respectfully, transcends the individual sphere, becoming a fundamental resource for guiding ethical conduct, strengthening social bonds, and fostering more humane professional environments. Furthermore, this classroom activity reaffirmed the relevance of pedagogical practices that combine theory and reflection, offering students the opportunity to develop critical awareness, ethical sensitivity, and social commitment, competencies essential to the training of professionals and leaders committed to the common good.